The relation of schneiderian membrane thickness and membrane perforation in sinus lift procedure: a systematic review - Sri Oktawati; Ingrid Neormansyah; Supiaty Supiaty (Journal of Dentomaxillofacial Science, 2018)
Objective: To evaluate the recent scientific evidence about the relation of schneiderian membrane thickness and sinus lift complications.Methods: A systematic search at pubMed and wiley online librarywas conducted to identify articles published between January 2013 to December 2017 about schneiderian membrane thickness relation with sinus lift complications. Manual selection of the full text articles was performed and from 133 articles found in initial searches, there were only 3 articles that compatible with the inclusion criteria.Results: The initial search resulted in 133 articles. All the full text articles were reviewed and selected based on inclusion criteria. There were 3 studies that compatible with inclusion criteria with 395 patients as subjects and 466 sinus lift or sinus augmentation proceduresperformed.Conclusion: The schneiderian membrane thickness might affects complications in sinus lift or sinus augmentation procedures, especially perforation of schneiderian membrane.